2019
DOI: 10.14295/bds.2019.v22i1.1631
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of high viscosity glass-ionomer and glass-carbomer with and without coating before and after hydrothermal aging

Abstract: Objective: The objective of this study was to evaluate the microleakage patterns of GIC and GGC with and without their protective surface coatings on enamel and dentin margins before and after aging. Material and Methods: Two rectangular cavities (height: 2 mm; width: 3 mm; depth: 1.5 mm) were prepared on each tooth at the cemento-enamel junction were prepared on human permanent molars (N=56) and the teeth were randomly assigned to be restored with one of the following: a) high viscosity glass-ionomer cement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Shebl et al [31] showed lower bond strength results of GCP when com pared to conventional GIC. Also, Munervveroglu et al [32] observed lesser microleakage scores in high viscos ity GIC (EQUIA Fil, C Corp.; Tokyo, Japan) when com pared to GCP. Moreover, Cehreli et al [33] conducted a study evaluating primary molars, and found higher microleakage scores in GCP, which presented internal and surface's cracks when compared to GIC.…”
Section: Discussionmentioning
confidence: 97%
“…Shebl et al [31] showed lower bond strength results of GCP when com pared to conventional GIC. Also, Munervveroglu et al [32] observed lesser microleakage scores in high viscos ity GIC (EQUIA Fil, C Corp.; Tokyo, Japan) when com pared to GCP. Moreover, Cehreli et al [33] conducted a study evaluating primary molars, and found higher microleakage scores in GCP, which presented internal and surface's cracks when compared to GIC.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the first null hypothesis was accepted. Münevveroğlu et al [ 31 ] reported that water sorption of a non-coated group of highly viscous GI in their study during thermal cycling led to volumetric expansion and marginal sealing comparable to the coated group. This is in agreement with previous studies, which found that non-coated surfaces of GI had higher values of water sorption than coated surfaces, potentially even exceeding the solubility levels of the material [ 32 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional GIs, including the GH tested herein, are highly susceptible to dehydration, especially during the early setting period [ 31 ]. Hence, in clinical service, a surface coating is needed to maintain water balance and reduce the resulting dehydration cracks [ 31 40 ]. However, such a coating was not used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations reported significantly lower microleakage in the resin-modified and conventional glass ionomer cement restorations in primary dentition coated with G-Coat Plus in primary teeth. 24,25 Conclusively, the surface coating would benefit all types of glass ionomer restorations. 26 The current study also assessed laser pretreatment, which showed no significant effect on the microleakage, compared with the control group.…”
Section: Discussionmentioning
confidence: 99%